2017
DOI: 10.1097/pec.0000000000000969
|View full text |Cite
|
Sign up to set email alerts
|

Lung Ultrasound as First-Line Examination for the Diagnosis of Community-Acquired Pneumonia in Children

Abstract: Lung ultrasound plays a significant role in the detection of CAP, not inferior to CXR. The aim of this study was to encourage the use of ultrasound as a first-line examination for CAP in children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
41
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 57 publications
(55 citation statements)
references
References 21 publications
3
41
0
2
Order By: Relevance
“…The role of LUS in determining the presence and features of pleural effusions is well known, as well the prediction of complicated outcomes when complex effusions are present; our study confirmed these finding (80%, P = .001).…”
Section: Discussionsupporting
confidence: 86%
“…The role of LUS in determining the presence and features of pleural effusions is well known, as well the prediction of complicated outcomes when complex effusions are present; our study confirmed these finding (80%, P = .001).…”
Section: Discussionsupporting
confidence: 86%
“…From this set of articles, 99 (12.6%) abstracts were identified for further analysis based on PRISMA analysis (Figure ). QUADAS review was applied to the 99 articles and 12 (1.5%) (Table ) were selected for inclusion in the meta‐analysis based on inclusion criteria, data collection, and lack of bias. All studies were observational.…”
Section: Resultsmentioning
confidence: 99%
“…[6][7][8][9] Moreover, those studies including follow-up lung US during CAP treatment did not include a detailed diagnostic lung US examination (done at time of diagnosis) and did not describe early lung US changes during the treatment in a detailed way. [10][11][12] In the following case series, we describe clinical and laboratory results as well as detailed lung US findings of 6 children with CAP, at baseline and 48 hours after beginning antibiotic treatment, showing the potential use of lung US in monitoring the response to antibiotic therapy.…”
mentioning
confidence: 99%
“…Nevertheless, the most of the published studies on this topic focused mainly on the accuracy of lung US in comparison with chest radiography in recognizing lung consolidations and bronchograms, without providing US details of the consolidations, such as the bronchogram position, morphologic characteristics, and dynamicity . Moreover, those studies including follow‐up lung US during CAP treatment did not include a detailed diagnostic lung US examination (done at time of diagnosis) and did not describe early lung US changes during the treatment in a detailed way …”
mentioning
confidence: 99%